PROBLEMATIKA HUKUM PEREDARAN VIRTUAL CURRENCY DAN PENGGUNAANNYA SEBAGAI ALAT PEMBAYARAN TRANSAKSI KOMERSIAL ELEKTRONIK DALAM SISTEM HUKUM DI INDONESIA - Anggraeni, Sindi Ayu; Sulistiyono, Adi (Jurnal Privat Law, 2020)
AbstractThis article describes how the legal problems in Article 21 Paragraph (1) of Law Number 7 of 2011 concerning Currency, Article 34 of Bank Indonesia Regulation No. 18/40 / PBI / 2016 concerning the Implementation of Payment Transaction Processing, and Article 8 Paragraph (2) of Bank Indonesia Regulation No. 19/12 / PBI / 2017 concerning the Implementation of Financial Technology concerning the circulation of virtual currency and its use as a means of payment for electronic commercial transactions in the legal system in Indonesia and how is the legal politics of Bank Indonesia to prevent the circulation of virtual currency as a payment instrument for electronic commercial transactions in Indonesia. This research is normative or doctrinal research with prescriptive and applied nature. The results showed that the legal problem of the circulation of virtual currency and its use as a means of payment for electronic commercial transactions in the legal system in Indonesia based on the principle of legal certainty lies in the virtual currency arrangement issued by Bank Indonesia only covering the use of virtual currency as a means of payment, but not mentioned regarding the rules for circulation of virtual currency. Furthermore, in this research, also outlines the legal politics of Bank Indonesia to prevent the circulation of virtual currency as a means of payment for electronic commercial transactions in Indonesia, given the absence of rules regarding the circulation of virtual currency.Keywords: Legal Problems; Virtual Currency; Payment Tools; Bank Indonesia’s Legal PoliticsAbstrakArtikel ini mendeskripsikan bagaimana problematika hukum dalam Pasal 21 Ayat (1) Undang-Undang Nomor 7 Tahun 2011 tentang Mata Uang, Pasal 34 Peraturan Bank Indonesia No. 18/40/PBI/2016 tentang Penyelenggaraan Pemrosesan Transasksi Pembayaran, dan Pasal 8 Ayat (2) Peraturan Bank Indoneisa No. 19/12/PBI/2017 tentang Penyelenggaraan Teknologi Finasial mengenai peredaran virtual currency dan penggunaannya sebagai alat pembayaran transaksi komersial elektronik dalam sistem hukum di Indonesia serta bagaimana politik hukum Bank Indonesia untuk mencegah peredaran virtual currency sebagai alat pembayaran transaksi komersial elektronik di Indonesia. Penelitian ini merupakan penelitian normatif atau doktrinal dengan sifat preskriptif dan terapan. Hasil penelitian menunjukan bahwa adanya problematika hukum peredaran virtual currency dan penggunaannya sebagai alat pembayaran transaksi komersial elektronik dalam sistem hukum di Indonesia berdasarkan asas kepastian hukum terletak pada pengaturan virtual currency yang di terbitkan oleh Bank Indonesia hanya mencakup mengenai penggunaan virtual currency sebagai alat pembayaran, tetapi tidak di sebutkan mengenai aturan peredaran virtual currency. Selanjutnya dalam penelitian ini, juga meguraikan politik hukum Bank Indonesia untuk mencegah peredaran virtual currency sebagai alat pembayaran transaksi komersial elektronik di Indonesia, mengingat tidak adanya aturan mengenai peredaran virtual currency.Kata Kunci: Problematika Hukum; Virtual Currency; Alat Pembayaran; Politik Hukum Bank Indonesia